Development and verification of a turbulent heat transport model for sodium-based liquid metal coolants - Rogozhkin, Sergey Aleksandrovich; Aksenov, Andrey Aleksandrovich; Zhluktov, Sergey Vasilievich; Osipov, Sergey Leonidovich; Sazonova, Marina Leonidovna; Fadeev, Ilia Dmitrievich; Shepelev, Sergey Fedorovich; Shmelev, Vladimir Vasilievich (Computational Continuum Mechanics, 2014)
Numerical simulation of heat-and-mass transfer in fast neutron reactors with sodium coolant performed based on commercial Computational Fluid Dynamics (CFD) software products is considered. It is shown that the Reynolds analogy used in most turbulence models cannot be applied to study the peculiarities of heat transport in liquid metal coolants. We present here results for a turbulent LMS (Liquid Metal Sodium) heat transport model capable of taking into account the unique characteristics of sodium coolants. Within the model, the turbulent Prandtl number expression is implemented, a correction that takes into account gravitational anisotropy of the turbulent heat flow is made, and the thermal wall function is introduced. The model is implemented in the bundled CDF FlowVision code, is compatible with theturbulence models and can be used in both the high (with wall functions) and low (without wall functions) Reynolds number calculations of sodium flow. The proposed LMS model has been verified on the basis of experimental data obtained in the TEFLU test facility (Karlsruhe, Germany). The test facility is intended to simulate mixing processes of sodium coolant flows of various temperatures. In the experiment, three flow regimes have been studied: “free convection” regime, “transient” regime, and “forced convection” regime. For these regimes, simulation results gained from the application of such commercial CFD bundled software products as ANSYS CFX, Star-CD, Fluent, and FlowVision with and without the LMS model are presented. It is shown that the results obtained using the bundled FlowVision software with the LMS model demonstrate better agreement with the experimental data compared to the data obtained using other bundled software products.